GENEREAL CHARACTERISTICS OF PHILOSOPHICAL LYRICS - Isroilov, G`ayrat (FILOLOGIYA UFQLARI JURNALI, 2022)
In recent years, such expressions as "philosophical poetry", "meditative lyricism", "intellectual poetry", "emotional-intellectual lyricism" are used in the study of literature. In addition, it is permeating the literary-scientific circulation. These are not in vain, of course. This is because the literary process itself requires the emergence of such diverse expressions. The essence of the artistic and aesthetic research carried out by our poets is that this analysis reveals different forms of expression.